Surrogacy with respect to criminal law - Konečná, Hana; Svatoš, Roman (Ústav státu a práva AV ČR, 2019)
Surrogacy is one of the most complicated procedures of assisted reproduction. The complexity of the procedure brings many legal problems, the main ones are determination of legal parenthood, enforceability of agreements, registration of the newborn, acceptance of the ways of recruiting a surrogate mother, acceptance of compensation, conditions of approach to the procedure, and circumstances of its implementation. The purpose of this paper is to describe this procedure with respect to criminal law. Considering the cases connected with surrogacy we usually somehow “quench” the results – a child is already here, despite being received in problematic ways, then we shall solve his or her interest. However, this child did not occur by chance, through a - problematic – act of an individual. The child was born because of the possibility of technology, and the application of technology is supervised by an institution. Society has a liability that must clearly delimitate the boundaries and possibilities of the use of technology, and consistently prosecute their possible violation.
Keywords: surrogacy; criminal law; liability; medical law; agreements